PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP UPAH MINIMUM PROVINSI JAMBI - M. Zahari MS (Universitas Batanghari Jambi, 2014)
Wage is one of the leading indicators to assess needed for decent living from labor who works in a company. The importance of providing wages to labor in accordance with his handiwork as well as the magnitude of the needs is a thing that must be considered by a businessman. This research is based on the phenomenon, whereby the granting of wage is for workers rights/labour in return to work, on the other hand employers saw the wage is cost. The purpose of this research is to find out and analyze the variables of economic growth and inflation against the minimum wage province of Jambi. The Data used in this study is secondary data during the year 2000-2013 sourced from BPS, Disnakertransos, Bappeda of Jambi province. Model analysis used is the regression equation is linear of multiple, being to the testing of hypotheses used test f and test t. The results were obtained regression coefficient of 2,538 variable economic growth. This means that if there is an increase in the economic growth of 1%, the provincial minimum wage will result in an increase of 2,538%. The while variable inflation of – 0,202. This means that if there is an increase in the inflation of 1% will result in the value of the minimum wage declined by 0,202%. The value of f count 6,054 > f table 3,98, and a significant degree 0,017 < alpha 0,05%. It means the independent variable (economic growth and inflation) influential positive and significantly affect the minimum wage jambi. Based on partial test (t test), variable economic growth and a significant positive effect on the Jambi provincial minimum wage, inflation variable is not significant and is worth a negative coefficient. This fact, indicate inflation can reduce the value of the money received by workers. Because even though the nominal value of the provincial minimum wage will increase but the value of the goods the purchasing power of workers will decrease, consequently the needs of everyday working life are not met.Keywords: economic growth, inflation, the provincial minimum wage